2011
DOI: 10.1097/01.aoa.0000400334.08022.4d
|View full text |Cite
|
Sign up to set email alerts
|

Maternal or Infant Antiretroviral Drugs to Reduce HIV-1 Transmission

Abstract: P regnancy-induced hypertension (PIH) or pregnancyaggravated hypertension (PAH) occurs in B7% of pregnant women, but whether medical treatment for mildto-moderate gestational hypertension is necessary is controversial. Knowledge of the long-term effects of prenatal exposure to antihypertensive medications is necessary so that risks to the infant can be weighed against benefits to the mother. This historical cohort study examined the functional development of children whose mothers were treated with labetalol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 0 publications
4
126
2
3
Order By: Relevance
“…89 Recent studies document that combining exclusive breastfeeding for 6 months with 6 months of antiretroviral therapy significantly decreases the postnatal acquisition of HIV-1. 90,91 There is no contraindication to breastfeeding for a full-term infant whose mother is seropositive for cytomegalovirus (CMV). There is a possibility that CMV acquired from mother' s milk may be associated with a late-onset sepsis-like syndrome in the extremely low birth weight (birth weight <1500 g) preterm infant.…”
Section: Contraindications To Breastfeedingmentioning
confidence: 99%
“…89 Recent studies document that combining exclusive breastfeeding for 6 months with 6 months of antiretroviral therapy significantly decreases the postnatal acquisition of HIV-1. 90,91 There is no contraindication to breastfeeding for a full-term infant whose mother is seropositive for cytomegalovirus (CMV). There is a possibility that CMV acquired from mother' s milk may be associated with a late-onset sepsis-like syndrome in the extremely low birth weight (birth weight <1500 g) preterm infant.…”
Section: Contraindications To Breastfeedingmentioning
confidence: 99%
“…The use of combined antiretroviral therapy (ART) and elective caesarean section has reduced MTCT rates to less than 2% in non-breastfeeding populations. Among breastfeeding populations, studies have demonstrated that timely antiretroviral therapy (ART) can reduce MTCT of HIV to 5% or less [2][3][4]. In view of these studies and more in 2010, UNAIDS set a target for member states to have virtual elimination of MTCT, defined as reducing MTCT to less than 5% and 90% reduction of new HIV infections among young children by 2015 [5].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of maternal use of cART in pregnancy for PMTCT is indisputable [1][2][3][4]. However, to maximize health outcomes among HEU children we need to understand the long-term implications of in-utero cART exposure and mitigate any identified adverse consequences to the greatest extent possible.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal triple antiretrovirals (cART) during pregnancy and breastfeeding are highly effective in preventing of mother-to-child HIV transmission (PMTCT) [1][2][3][4]. As a result, WHO guidelines recommend universal maternal use of triple ART (cART) during pregnancy and breastfeeding as one PMTCToption [5].…”
Section: Introductionmentioning
confidence: 99%